EVALUASI PENGENDALIAN INTERN SISTEM INFORMASI AKUNTANSI PENERIMAAN KAS ATAS PENJUALAN JASA KAMAR PADA BIG FISH HOTEL - Modim, Arif Rahman; Tinangon, Jantje J.; Pangerapan, Sonny (JURNAL RISET AKUNTANSI GOING CONCERN, 2018)
Organizations to achieve sustainable position and possible opportunities requires efficient information systems. The purpose of the study is to evaluate the implementation an internal control in accounting information system cash receipt in Big Fish hotel (Piere Tendean Number. 107-108 Boulevard Manado). This research approach is qualitative descriptive with the type of case study research. Types of data used are primary data and secondary data. Data were collected through a preliminary survey, field research, observation, interviews, and documentation. The result show that accounting informations systems cash receipt at this hotel has been have well internal control. Although there were many problem has found, that there is no a job rotation to maintain employee independence in carrying out their duties, he absence of an internal supervisory unit that can guarantee security and finances, there is no surprising audit to check accurately.Keywords : Accounting Information System, Cash Receipt, Internal Control